Evolution of human socio-cultural and ecological traits: a phylogenetic (supertree) approach - Duda, Pavel (Jihočeská univerzita, 2011)
Human species display complex intraspecies population structure and unparalleled behavioral and cultural diversity. In order to elucidate human population history and pattern of evolutionary change of socio-cultural and ecological traits, the first composite phylogenetic tree of 574 human populations (ethno-linguistic groups) was created on the basis of 129 recently published phylogenetic hypotheses based on genomic, genetic and linguistic data, utilizing supertree method matrix representation with parsimony. Subsequently, 56 selected socio-cultural and ecological characters based on ethnographic cross-cultural data were optimized on topology of obtained supertrees in order to reconstruct patterns of evolutionary change and states present in ancestral populations. The results are discussed in the light of recent studies of human phylogeography and cultural phylogenetic studies.
Evolution of human socio-cultural and ecological traits: a phylogenetic (supertree) approach
Keywords: human evolution; cultural phylogenetics; cross-cultural; supertree; MRP; ancestral states; human evolution; cultural phylogenetics; cross-cultural; supertree; MRP; ancestral states